Strategi Komunikasi Pengelolaan Sampah di Kota Ambon: Perspektif SCCT dan Konstruksi Sosial - Christ J. Belseran; Ridzki Rinanto Sigit (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the waste management communication strategy by the Ambon City government using the Situational Crisis Communication Theory (SCCT) and the Social Construction Theory. This research employed a qualitative case study approach in the riverbank areas of Way Batu Merah and Way Ruhu Galala. The results show that the behavior of disposing waste into the river is a long-standing social construction reinforced by weak infrastructure and public communication. The government’s communication strategy still relies heavily on bolstering and diminishing approaches, while rebuilding and attenuating are not yet optimal. The study recommends integrating the Theory of Planned Behavior (TPB) to understand community behavioral tendencies better and to develop culturally rooted public communication strategies.